Saberes destinados à formação de professores em Alagoas: o Compêndio de Pedagogia Prática (1886) de Joaquim José de Araujo - Santos, Regina Brito Mota dos (2019)
The present work investigated the knowledge dedicated to the teachers graduation at the Alagoas’ province at the last decades of XIX century, using the Compêndio de Pedagogia Prática (1886) of the teacher and doctor Joaquim José de Araujo. In this manner, laws, decrees, journals and official reports of that season were used as second sources to the rules system comprehension that governed the production, control and circulation of the studied opus and established the parameters to the teachers graduation at the Alagoas’ province. The printout was destined to the use of teachers at exercising or primary graduation at the Curso Normal de Maceió, and had presented some practical and theoretical indications series based in Jean Baptiste Daligault’s propositions, at his Curso Prático de Pedagogia (1870). The context of the opus production and circulation disseminated the thinking that the nation concept reformulation should pass by the schools knowledge, turning necessary the compendiums production that should control and rationalize the teachers graduation and actuation. The achieved studies about the theme verify this printouts paper at the Pedagogy constitution as science and school subject, by the transmitting and legitimating of the “knowing to be” an the “knowing to do” of the XIX century teaching. At this work, we have discussed the destined knowledge to the teachers graduation based in representation and appropriation categories developed by Roger Chartier (1990, 1998, 2002), and in the historical concept defined by ulia (2011). The principal search results point the Compêndio de Pedagogia Prática (1886) as an important consult material, legitimating and circulation of knowledge and teaching practices at the Alagoas’ province destined to the subjects that at the first time had kept contact with the teaching of practice competency.